Revision of the EPICA Dome C CO2 record from 800 to 600 kyr before present. Issue 2 (23rd January 2015) - Bereiter, Bernhard; Eggleston, Sarah; Schmitt, Jochen; Nehrbass‐Ahles, Christoph; Stocker, Thomas F.; Fischer, Hubertus; Kipfstuhl, Sepp; Chappellaz, Jerome
Abstract: The European Project for Ice Coring in Antarctica Dome ice core from Dome C (EDC) has allowed for the reconstruction of atmospheric CO2 concentrations for the last 800, 000 years. Here we revisit the oldest part of the EDC CO2 record using different air extraction methods and sections of the core. For our established cracker system, we found an analytical artifact, which increases over the deepest 200 m and reaches 10.1 ± 2.4 ppm in the oldest/deepest part. The governing mechanism is not yet fully understood, but it is related to insufficient gas extraction in combination with ice relaxation during storage and ice structure. The corrected record presented here resolves partly ‐ but not completely ‐ the issue with a different correlation between CO2 and Antarctic temperatures found in this oldest part of the records. In addition, we provide here an update of 800, 000 years atmospheric CO2 history including recent studies covering the last glacial cycle. Key Points: Analytical bias discovered in the EPICA Dome C CO2 record Bias is confined to 13 ppm and the deepest 200 m (600–800 kyr B.P.) Corrected and updated ice core CO2 compilation is provided